From ink to the internet an exploratory study on the digital adaptations implemented by Central Luzon community newspapers - Mamorbor, Marñino Giebon S.; Rara, Ma. Cristina I. (Quezon City University of the Philippines Diliman, 2025)
This thesis examines how Central Luzon community newspapers have adapted and developed in the face of rapid digitalization in the journalism and newspaper industry. Using a qualitative research approach, seven employees and staff members from three community newspapers were interviewed about the effects of digitalization in their publications. Although in decline, these newspapers are given second wind as they integrated new technology into their operations, including editing and layouting, publishing, and communication. Social media, particularly, gave these publications a bigger audience and more business opportunities. While general perception is positive among the publications’ staff, most still express missing elements of community and camaraderie that were once present in previous iterations of their newsroom operations. Even with this progress, community journalists still wish for the continued growth and preservation of their original endeavor: the community newspaper.
Thesis
Keywords: Newspapers -- Digitization -- Philippines; Mass media -- Technological innovations -- Philippines -- Central Luzon; Community newspapers -- Philippines -- Central Luzon; Electronic publishing -- Philippines